Between Jerusalem and Athens ethical perspectives on culture, religion, and psychotherapy - Dueck, Alvin C. 1943- (Grand Rapids, MI Baker, 1995)
Includes bibliographical references and index.
Keywords: Psychologists -- professional ethics; Psychology -- moral and ethical aspects; Psychology -- religious aspects -- Christianity